Noncanonical calcium binding motif controls folding of HopQ1, a Pseudomonas syringae type III secretion effector, in a pH-dependent manner - Fabian Giska; Wojciech Rymaszewski; Malgorzata Lichocka; Marcin Piechocki; Jakub Kwiatkowski; Jarosław Poznański; Magdalena Górecka; Magdalena Krzymowska (Scientific Reports)
Abstract Virulence of many gram-negative bacteria relies upon delivery of type three effectors into host cells. To pass through the conduit of secretion machinery the effectors need to acquire an extended conformation, and in many bacterial species specific chaperones assist in this process. In plant pathogenic bacterium Pseudomonas syringae, secretion of only few effectors requires the function of chaperones. This raises a question how chaperone-independent effectors achieve an appropriate conformation for the secretion. One such mechanism was previously described for AvrPto. It contains a pH-sensitive switch, which is involved in unfolding of the effector at the mildly acidic pH corresponding to the pH value of the bacterial cytosol, and refolding at the neutral pH. Therefore, it was proposed that the switch facilitates first translocation of AvrPto and then its maturation once the effector reaches the cytoplasm of host cell. Here we show that an atypical motif of HopQ1, another effector of P. syringae, reversibly binds calcium in pH-dependent manner, regulating the effector thermal stability. Therefore, we propose a model that HopQ1 traversing through the type three secretion system encounters conditions that maintain its extended conformation, while upon delivery into host cell the effector undergoes refolding.